Α‐Methylene‐β‐Lactone Scaffold for Developing Chemical Probes at the Two Ends of the Selectivity Spectrum. (11th November 2020) - Wang, Lei; Riel, Louis P.; Bajrami, Bekim; Deng, Bin; Howell, Amy R.; Yao, Xudong
Abstract: The utilities of an α‐methylene‐β‐lactone (MeLac) moiety as a warhead composed of multiple electrophilic sites are reported. We demonstrate that a MeLac‐alkyne not only reacts with diverse proteins as a broadly reactive measurement probe, but also recruits reduced endogenous glutathione (GSH) to assemble a selective chemical probe of GSH‐β‐lactone (GSH‐Lac)‐alkyne in live cells. Tandem mass spectrometry reveals that MeLac reacts with nucleophilic cysteine, serine, lysine, threonine, and tyrosine residues, through either Michael or acyl addition. A peptide‐centric proteomics platform demonstrates that the proteomic selectivity profiles of orlistat and parthenolide, which have distinct reactivities, are measurable by MeLac‐alkyne as a high‐coverage probe. The GSH‐Lac‐alkyne selectively probes the glutathione S‐transferase P responsible for multidrug resistance. The assembly of the GSH‐Lac probe exemplifies a modular and scalable route to develop selective probes with different recognizing moieties. Abstract : Create high‐coverage and selective probes from multi‐reactive scaffold : An α‐methylene‐β‐lactone (MeLac) scaffold provides new paths to create reactivity‐ and proximity‐driven covalent probes for chemical proteomics. Multiple reactivities of the MeLac warhead allows it to react with different protein nucleophiles through distinct mechanisms, and to assemble highly selective proteomics probes. MeLac‐derived probes have potential to make significant impacts on drug discovery and development.